The Immunomodulatory Potential of tolDCs Loaded with Heat Shock Proteins - van Eden, Willem; Jansen, Manon A. A.; de Wolf, A Charlotte MT; Ludwig, Irene S.; Leufkens, Paul; Broere, Femke (Frontiers in Immunology, 2017)
Disease suppressive T cell regulation may depend on cognate interactions of regulatory T cells with self-antigens that are abundantly expressed in the inflamed tissues. Heat shock proteins (HSPs) are by their nature upregulated in stressed cells and therefore abundantly present as potential targets for such regulation. HSP immunizations have led to inhibition of experimentally induced inflammatory conditions in various models. However, re-establishment of tolerance in the presence of an ongoing inflammatory process has remained challenging. Since tolerogenic DCs (tolDCs) have the combined capacity of mitigating antigen-specific inflammatory responses and of endowing T cells with regulatory potential, it seems attractive to combine the anti-inflammatory qualities of tolDCs with those of HSPs.